EU climate leadership: five building blocks for ambitious action - Clara Brandi; Steffen Bauer; Pieter Pauw; Sander Chan; Okka Lou Mathis (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The United Nations (UN) climate summit (COP 21) in Paris is the most important opportunity for years to come to organise effective collective action at the international level to stabilise global warming at 1.5 degrees Celsius (°C), or at least limit it to a maximum of 2°C; facilitate the transition towards a zero-carbon economy; and mobilise significant financial resources to adapt to climate change, particularly in the most vulnerable countries. The European Union (EU) is in a unique position to contribute decisively to these ends. With its climate pledge from March 2015, the EU has made explicit what it considers to be a fair offer, in terms of reducing greenhouse gas emissions. However, to further an ambitious and fair deal, the EU should be prepared to offer even more in the key negotiating fora, especially regarding adaptation and finance. With the negotiations towards COP 21 in full swing and the EU's negotiation mandate fixed, however, the real work will begin after Paris. Five building blocks will be of particular importance to demonstrate European leader-ship: (1) mitigation, (2) adaptation, including the issue of loss and damage (L&D), (3) climate finance, (4) a framework for non-state climate actions and (5) the building of ambitious alliances. 1. Mitigation: The Intended Nationally Determined Contribution (INDC) of the EU and its member states represents an important step in the right direction, but it is not ambitious enough to really make the EU a climate leader. The INDC target of 40 per cent emission reductions by 2030 is based on a scenario of 80 per cent decarbonisation by 2050. This puts the EU at the lower end of its long-term goal of 80–95 per cent by mid-century. Attaining the 40 per cent target by 2030 does not necessarily enable the EU to reach a goal of 80 per cent by 2050, even if it were on track to reach its 40 per cent target in 2030 – which it is not. 2. Adaptation and L&D: The international community has waited too long and acted too weakly to fully avoid dangerous climate change, meaning more vulnerable countries and populations will be increasingly affected by severe impacts of climate change. Action on adaptation as well as L&D is therefore crucial for COP 21 and beyond, and the EU should be seen as treating these issues with the same priority and urgency as mitigation. 3. Climate finance: Climate finance is the most straight-forward way to demonstrate an international commitment to fight climate change and its impacts. To demonstrate resolve and credibility, the EU's contributions for mitigation and adaptation will need to be made in addition to its conventional development finance. 4. A framework for non-state climate actions: The EU has been a frontrunner in promoting greater engagement of non-state and subnational actors in global climate policy. It should thus support a long-term action agenda and policy framework to facilitate and galvanise bottom-up climate actions. 5. Ambitious alliances: Since 2011, the EU has made considerable efforts to revitalise its external climate action and related diplomacy. Paris will be a vantage point to capitalise on new opportunities.
Keywords: 330; Klimawandel; Energie